Web-Based Electronic Goods Sales Application Design - Rafi Farizki; Lutfi Mualiman; Freddy Wicaksono; Fhrizz S. De Jesus; Meritorious Autonomous; Vo Hung Cuong (Ridwan Institute, 2022)
The development of technology, especially internet-based technology, is increasing, including sales information system technology or so-called web online stores that can be used to purchase products simply by logging into the web, selecting the preferred goods and paying using a transfer system, the goods will be delivered to the address which is aimed. In Indonesia, the development of sales information systems is very reasonable and will continue to increase rapidly with the spread of the internet to all corners of the region. The purpose of this research is to know that this sales application system can already be used online. The method used is to use system design analysis. The results showed that in making these electronic goods sales application using the PHP programming language with MYSQL Database. The application for selling electronic goods is also known to have three important aspects, namely: login menu, admin dashboard, and payment page.